O-110 Endometrial preparation for FET: HRT vs. Natural cycle. (30th June 2022) - Polyzos, N.P
Abstract: : Frozen-thawed embryo transfer (FET) cycles have increased dramatically over the past decade, mainly due to the introduction of vitrification as a more efficient method of cryopreservation, and the increase of the freeze-all strategy in order to reduce the risk of OHSS. Planning of FET cycles is a key step for the implantation of the frozen-thawed embryos since it allows the synchronization of the endometrium with the developmental stage of the embryo. Endometrial preparation can be achieved either through hormonal replacement treatment (HRT) by an artificial cycle using exogenous estrogen administration for the development of the endometrium and subsequent administration of exogenous progesterone for its secretory transformation (AC-FET) or via a natural cycle, following the detection of LH surge (NC-FET), or the trigger of ovulation with human chorionic gonadotrophin (mNC-FET). The scope of the current presentation is to provide an overview of the different methods of endometrial preparation for FET cycles, their advantages, and disadvantages, and the evidence regarding clinical but also adverse obstetrical and perinatal outcomes, following each different protocol. Trial registration number: